A systematic study on molecular planarity and D–A conformation in thiazolothiazole- and thienylenevinylene-based copolymers for organic field-effect transistors. Issue 39 (11th August 2017) - Lim, Dae-Hee; Jang, Soo-Young; Kang, Minji; Lee, Sehyun; Kim, Yeong-A; Heo, Youn-Jung; Lee, Min-Hye; Kim, Dong-Yu
Abstract : The new D–A type conjugated polymers were synthesized to confirm that structural characteristics, such as the presence of coplanar units and a D–A conformation. Abstract : A new donor–acceptor type conjugated polymer (P1 ) composed of thiazolothiazole (TzTz) and thienylenevinylene (TV) units was synthesized to confirm that structural characteristics, such as the presence of coplanar units and a D–A conformation in the polymer main chain, can have an effect on charge carrier transport in high performance organic field-effect transistors.P1 was compared with two polymers that had bithiophene (BiTh) units instead of TV units (P2 ) or thienothiophene (TT) units in the place of TzTz units (P3 ) to investigate the relationship between the molecular structure and polymer properties.P1 had a higher order of orientation thanP2 due to the rigid and planar structure caused by the presence of the TV unit inP1 compared to the distorted structure ofP2 . The effect of the D–A type configuration inP1 was also confirmed by demonstrating its stronger intermolecular interactions and more effective hole and electron transport compared with that of the D–D type polymerP3 . Thus, in contrast toP2 (with a hole mobility of 0.076 cm 2 V −1 s −1 and an electron mobility of 0.0025 cm 2 V −1 s −1 ) andP3 (with a hole mobility of 0.2 cm 2 V −1 s −1 only), P1 exhibited higher ambipolar charge carrier mobilities (1.66 cm 2 V −1 s −1 of holes and 0.05 cm 2 V −1 s −1 of electrons).